Changes In Plasma NPY, IL-1β And Hypocretin In People Who Died By Suicide - Lu J (Dove Medical Press, 2019)
Jing Lu,1 Shangda Li,1 Haimei Li,1 Tingting Mou,1 Lihong Zhou,2 Bochao Huang,1 Manli Huang,1 Yi Xu1 1The Key Laboratory of Mental Disorder Management in Zhejiang Province, Department of Psychiatry, First Affiliated Hospital, College of Medicine, Zhejiang University, Zhejiang University Brain Research Institute, Hangzhou, Zhejiang Province, People’s Republic of China; 2Institute of Criminal Science and Technology, Hangzhou Public Security Bureau, Hangzhou, Zhejiang Province, People’s Republic of ChinaCorrespondence: Yi Xu; Manli HuangThe Key Laboratory of Mental Disorder Management in Zhejiang Province, Department of Psychiatry, The First Affiliated Hospital, Zhejiang University School of Medicine, 79 Qing Chun Road, Hangzhou 310003, People’s Republic of ChinaTel/fax +86-571-8723-5995Email xuyizju@zju.edu.cn; huangmanli@zju.edu.cnPurpose: There is growing evidence showing that inflammatory cytokines and neuropeptides may be involved in the pathophysiology of suicidal behavior. However, studies have yielded contradictory data, and no biological markers that help predict suicide have been identified. This study aimed to identify biological patterns, such as NPY, IL-1β and hypocretin plasma levels, in people who died by suicide.Patients and methods: Twenty-two people who died by suicide compared with 22 controls matched for age and sex were studied. In suicide and control subjects, we estimated the levels of NPY, IL-1β and hypocretin in plasma using enzyme-linked immunosorbent assay. The data are presented as the median (25th–75th percentile).Results: We found (1) a significant elevation in plasma NPY levels in suicide subjects versus control subjects (suicide: 11.38 (9.380–16.55); controls: 8.95 (7.590–10.93); P=0.013), and plasma NPY concentrations were approximately 62% higher in suicide subjects than those in control subjects; (2) a significant decrease in plasma IL-1β concentrations between suicide and control subjects (suicide: 121.1 (82.97–143.0); controls: 425.9 (233.1–835.3); P<0.001) as well as a decrease in IL-1β concentrations by almost 80%; and (3) no significant difference in plasma hypocretin levels between suicide and control subjects (suicide: 16.62 (13.62–25.77); controls: 21.63 (14.97–29.72); P=0.356).Conclusion: Our results suggest that plasma NPY and IL-1β were related with suicide behavior rather than to suicide causes or suicide method. Specific combinations of plasma biomarkers may discriminate between types of suicidal behaviors and indicate increased risk for future suicide attempts.Keywords: plasma biomarkers, suicide behavior, suicide causes, suicide method